The E1B19K-deleted oncolytic adenovirus mutant AdΔ19K sensitizes pancreatic cancer cells to drug-induced DNA-damage by down-regulating Claspin and Mre11 - Pantelidou, Constantia (Oncotarget, 2016)
Adenovirus-mediated sensitization of cancer cells to cytotoxic drugs depends on simultaneous interactions of early viral genes with cell death and survival pathways. It is unclear what cellular factors mediate these interactions in the presence of DNA-damaging drugs. We found that adenovirus prevents Chk1-mediated checkpoint activation through inactivation of Mre11 and downregulation of the pChk1 adaptor-protein, Claspin, in cells with high levels of DNA-damage induced by the cytotoxic drugs gemcitabine and irinotecan. The mechanisms for Claspin downregulation involve decreased transcription and increased degradation, further attenuating pChk1-mediated signalling. Live cell imaging demonstrated that low doses of gemcitabine caused multiple mitotic aberrations including multipolar spindles, micro- and multi-nucleation and cytokinesis failure. A mutant virus with the anti-apoptotic E1B19K-gene deleted (AdΔ19K) further enhanced cell killing, Claspin downregulation, and potentiated drug-induced DNA damage and mitotic aberrations. Decreased Claspin expression and inactivation of Mre11 contributed to the enhanced cell killing in combination with DNA-damaging drugs. These results reveal novel mechanisms that are utilised by adenovirus to ensure completion of its life cycle in the presence of cellular DNA damage. Taken together, our findings reveal novel cellular targets that may be exploited when developing improved anti-cancer therapeutics.